THE SCHEMATIC STRUCTURE OF ENGLISH AND INDONESIAN RESEARCH ARTICLE INTRODUCTIONS - Rahman, Kasyfur; Sofwan, Ahmad (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2012)
The article reports an investigation on the differences between the schematic structure of English and Indonesian research article introduction. By selecting thirty research articles from each group and analysing them using the CARS model (1990, 2004), this study has unravelled several differences. At the macro level, the English articles respectively have a higher percentage of reviewing items of previous research, indicating gap, and summarising methods. While their Indonesian counterparts tend to have a greater deal with making topic generalisations, presenting positive justifications, and stating the value of the present research. In addition, while the Indonesian articles have more unidentified schematic elements and lack outlining the structure of paper, the English ones demonstrate a higher degree of move reiteration. At the micro level, the English articles are characterised by the use personal deixes as self-mention, and more variation of linguistic clues in claiming centrality. On the other hand, their Indonesian counterparts are depicted by the absence of self-mention, the use of code mixing, and a major tendency in using amplifiers and evaluative adjectives in claiming centrality. These differences might be partially influenced by the writersÃ¢â¬â¢ culture, knowledge, editorial policy, social environment, and in certain cases, the technical problems.